Real-time stochastic detection of multiple neurotransmitters with a protein nanopore. - Boersma, A; Brain, K; Bayley, H (2012)
The detection of several different neurotransmitters with the same sensor in real-time would be a powerful asset to the field of neurochemistry. We have developed a detector for a broad range of neurotransmitters including amino acids, catecholamines, and nucleotides, which relies on the reversible binding of the analytes to a copper(II) complex within an engineered protein nanopore.